Liquid Chromatography-Tandem Mass Spectrometric Assay for Determination of Stavudine in Human Plasma - Fengdan Jin (Journal of Spectroscopy)
A LC-MS/MS method for determination of stavudine in human plasma was established and validated, and it was applied to the pharmaceutical formulations bioequivalence study. 0.5 mL plasma sample was extracted by liquid-liquid extraction. Stavudine was detected by a LC-MS/MS system. The pharmacokinetic parameters of stavudine in different formulations were calculated by noncompartment model statistics. The method was linear over the concentration ranges 5.00–1000 ng/mL in plasma. The intra- and interassay relative standard deviation (RSD) was <10%. The average accuracies for the assay at three concentrations (5.00, 80.0, and 900 ng/mL) were from 100.2% to 102.5%. Pharmacokinetic parameters of stavudine reference formulation were obtained as follows: Tmax was 0.6±0.2 h, Cmax was 480.7±150.9 g/L, t1/2 was 1.7±0.4 h, and AUC0-t was 872.8±227.8 g·h/L, and pharmacokinetic parameters of stavudine test formulation were obtained as follows: Tmax was 0.5±0.2 h, Cmax was 537.5±178.5 g/L, t1/2 was 1.7±0.3 h, and AUC0-t was (914.1±284.5) g·h/L. Calculated with AUC0-t, the bioavailability of two formulations was 105.0%.